(untitled) (Baghdad Science Journal, 2025)
The research aims to find ways to minimize the use of quantities of chemical fertilizers in agriculture in order to get to an environment that is free of contaminants. Magnetized water technology used in the experience of planting seeds of tomatoes Thomson type to obtain a higher efficiency to absorb fertilizer NRK in the protected environment of the period from February to June. Magnetized water system used locally made levels Gaues (4800,2500,1500) concentrations of 50 to 100% for each level and the rate of (4) replicates, and results indicated that the severity of the magnet (4800 Gaues) and a concentration of 50% gave the highest percentage of tomato fruit size and intensity ( 1500 Gaues) and a concentration of 100% did not give any increase in the proportion of tomatoes or fruit size, but did not give three levels increase in the amount of tomato crop.